Mothering Behind Bars: Evaluating the Effectiveness of Prison Nursery Programs on Recidivism Reduction. (November 2019) - Dodson, Kimberly D.; Cabage, LeAnn N.; McMillan, Shaina M.
The purpose of this study is to conduct a comprehensive evidence-based review of evaluation studies of prison nursery programs to determine whether they are effective in reducing recidivism. Seven studies evaluating the effectiveness of prison nursery programs are examined and classified using the Maryland Scientific Methods Scale. The results show some empirical evidence for the capacity of prison nursery programs to reduce recidivism. However, weak methodological research designs and insufficient statistical analyses led us to classify the effectiveness of prison nursery programs as "unknown." Suggestions for improving the methodological quality of studies examining prison nursery programs and directions for future research are discussed.